What are the composition rules of these sentences?

  • let the cat out of the bag
  • take off clothes
  • burn the candle at both ends

For example: the C-Rule of "bring home the bacon" is: VC("the bacon",NP,AJ2)VA([home],A,AJ1);

Here is also a good reference to explain the C-Rules: "C-rule" in the UNL Wiki.

  • Welcome! Have you tried answering the question yourself? If you can show this, it would make it more likely that others will take the time to help you.
    – robert
    Jul 11, 2014 at 8:17
  • yes I tried and I already answered one of them, I solved this one : take off clothes, the composition rule of it is :VA([off],A)VC([clothes],N); Jul 11, 2014 at 13:34
  • and i am trying to solve this one too :let the cat out of the bag. and this is the last thing i have reached: VA("out of the bag",PP)VC("the cat",NP); but this is wrong unfortunately Jul 11, 2014 at 14:24
  • @robert please help me if you can Jul 11, 2014 at 15:20
  • You realize that this is just one way -- and hardly a standard way at that -- of stating the "composition rules". Nobody but your teacher will ever want you to be able to state them this way, and certainly nobody but your teacher and the rest of the students in the class will ever understand it if you do.
    – jlawler
    Jul 11, 2014 at 15:37

1 Answer 1


Many people seem to be under the impression that context free phrase structure grammar (cfpsg) cannot describe discontinuous constituents. It can, and these are good examples to show that. Suppose that we can derive a new phrase structure rule (psr) by composing two psrs, according to the scheme [A -> x B y](B -> z) = A -> xzy, where A, B are non-terminal symbols and x, y, z are strings of non-terminal and terminal symbols. The notation [rule i](rule j) = rule k means that rule i applies to rule j to derive rule k.

Then, for your examples, we have:

a. [VP -> let NP out of the bag](NP -> the cat) = VP -> let the cat out of the bag
b. [VP -> take off NP](NP -> clothes) = VP -> take off clothes
c. [VP -> burn NP at both ends](NP -> the candle) = VP -> burn the candle at both ends

Example b., as it stands, is of course not a discontinuous constituent, but with a particle movement rule, [VP -> take off NP] ==> [VP -> take NP off], can be converted into one. (A constituent is a string of terminal symbols such as "take off", and a discontinuous constituent is a string of terminal symbols interrupted by a non-terminal, such as "take NP off".)

This shows that the composition of discontinuous constituents, such as the ones involved in your examples, can be simply represented within a very well known theory, cfpsg, without appealing to an idiosyncratic framework.

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.